Treatment of fungal infections: an update - Antonietta Giannattasio; Claudio Veropalumbo; Lidia Mari; Valentina Marra; Maria Vittoria Andreucci; Letizia Capasso; Francesco Raimondi (Hygeia Press di Corridori Marinella, 2014)
Fungal infections represent a serious problem in neonatal intensive care units (NICUs) worldwide. Preterm infants are a vulnerable population for major events and adverse sequelae from fungal sepsis. The primary fungus of concern in neonates is C. albicans, whose colonization is associated with devastating complication and high rate of mortality. Among the risk factors responsible for development of invasive fungal infections, previous mucosal and skin colonization are of primary importance. Fungal colonization in neonates may be secondary to either maternal transmission or nosocomial acquisition in the nursery. Antifungal prophylaxis is currently applied in different NICUs and in various patients groups with successful results. Prophylactic drugs can include oral nystatin and oral or intravenous fluconazole. To date, antifungal prophylaxis with fluconazole is the recommended approach for neonates lower than 1,000 g and/or 27 weeks' gestation or less, manly in NICUs with relatively high frequency of invasive candidiasis. First-line treatment of invasive fungal infections includes amphotericin B deoxycholate, lipid preparations of amphotericin B, fluconazole, or micafungin. However, data on pharmacokinetic, schedule treatment and appropriate dosage of antifungal agents in neonates, mainly in premature, are still limited. Future strategies to reduce neonatal morbidity and mortality derived from invasive fungal infections include new echinocandins not yet approved for neonatal use (caspofungin or anidulafungin) and other adjuvant treatments as intravenous immunoglobulin, lactoferrin or probiotics. Since current therapies for systemic fungal diseases are not universally successful and morbidity remains high, future efforts will be also focused on better prevention of fungal diseases and understanding of appropriate dosing schedule of the available antifungal agents.   Proceedings of the 10th International Workshop on Neonatology · Cagliari (Italy) · October 22nd-25th, 2014 · The last ten years, the next ten years in Neonatology Guest Editors: Vassilios Fanos, Michele Mussap, Gavino Faa, Apostolos Papageorgiou